Hypolipidemic effects of silymarin are not mediated by the peroxisome proliferator-activated receptor alpha - Orolin, J; Vecera, R; Jung, D; Meyer, U A; Skottová, N; Anzenbacher, P (Xenobiotica; the fate of foreign compounds in biological systems, 2007)
Silymarin is widely used in supportive therapy of liver diseases. It has been shown lately that silymarin has beneficial effects on some risk factors of atherosclerosis owing to its hypolipidemic properties. PPARalpha plays a key role in lipid metabolism and homeostasis as its target genes are involved in catabolism of fatty acids by beta-oxidation (e.g. acyl-CoA oxidase) and by omega-oxidation (e.g. cytochrome P4504A). Here we studied the possibility that hypolipidemic effects of silymarin may be mediated by PPARalpha. Rats fed with a high-cholesterol diet with either silymarin or fenofibrate (as a positive control both for PPARalpha expression as well as for lipid determination) were used. The effects of silymarin on expression of PPARalpha both at the mRNA (including selected target genes) as well as the protein level were determined. In parallel, the levels of cholesterol and triacylglycerols were determined. Our results confirmed the hypolipidemic effects of silymarin and demonstrated that these effects are probably not mediated by PPARalpha because of unchanged mRNA levels of PPARalpha target genes. Furthermore, this work shows for the first time that cholesterol itself inhibits expression of CYP4A mRNA.
Keywords: krysa rodu Rattus; Animals; exprese genu; PPAR alpha; Silymarin; Rats; mužské pohlaví; zvířata; Male; Hypolipidemic Agents; Rats, Wistar; silymarin; hypolipidemika; Gene Expression; potkani Wistar; PPAR alfa